Developmental and water deficit-induced changes in hydraulic properties and xylem anatomy of tomato fruit and pedicels. (9th January 2021) - Li, Hao; Zhang, Xianbo; Hou, Xuemin; Du, Taisheng
Abstract : A decline in water transport capacity during fruit development in tomato does not occur in the xylem pathway leading up to the fruit, but within the fruit itself, and the hydraulic resistance of the xylem pathway is not significantly influenced by water deficit. Abstract: Xylem water transport from the parent plant plays a crucial role in fruit growth, development, and the determination of quality. Attempts have been made to partition the hydraulic resistance of the pathway over the course of development, but no consensus has been reached. Furthermore, the issue has not been addressed in the context of changing plant and fruit water status under water deficit conditions. In this study, we have conducted a rigorous investigation into the developmental changes that occur in the hydraulic properties of tomato fruits and their pedicels under well-irrigated and water deficit conditions, based on hydraulic measurements, fruit rehydration, dye-tracing, light and electron microscopy, and flow modeling. We found that a decline in water transport capacity during development did not occur in the xylem pathway leading up to the fruit, but within the fruit itself, where the effect might reside either inside or outside of the xylem pathway. The developmental pattern of the hydraulic resistance of the xylem pathway was not significantly influenced by water deficit. The changes in xylem flow between the fruit and the parent plant resulting from the reduced driving force under water deficit could explain the reduced accumulation of water in the fruit. This study provides new insights that aid our understanding of xylem water transport in fleshy fruits and its sensitivity to water deficit from a hydraulic perspective.